STRUCTURE OF THE INFORMATION COMPONENT OF PROFESSIONAL COMPETENCE OF THE FUTURE TEACHER (Pedagogy of Higher and Secondary Education, 2022)
The article investigates the information components structure of future teachers' professional efficlency and defines the contents of information efficiency.
Keywords: education system informatization; information efficiency; professional efficiency